Self Esteem dan Self Efficacy: Faktor Pembentuk Organizational Citizenship Behaviour di Badan Usaha Milik Negara - Mochamad Soelton (Journal of Fundamental Management (JFM), 2021)
This research aims to examine and analyze the effect of self esteem and self efficacy on employee performance with organizational citizenship behaviour as an intervening variable for employees of PT. PGN MAS. The object of this research is 75 employees of PT. PGN MAS. The approach used in this research is Component orVariance Based Structural Equation Model with analysis tool Smart-PLS. The results showed self esteem that has positive and significant effect on organizational citizenship behaviour. Self efficacy that has positive and significant effect on organizational citizenship behaviour.organizational citizenship behaviour that has positive and significant effect on employee performance. Self Esteem that has positive and significant effect on employee performance.Self Efficacy that has positive and significant effect on employee performance.Keywords:Organizational Citizenship Behaviour, Self Esteem, Self Efficacy,Employee Performance